Paget’s Disease in an Omani: Long-term Improvement Following a Single Injection of Zoledronic Acid - Elshafie, Omayma (Oman Med J, 2016)
Paget’s disease of bone is a patchy skeletal disorder characterized by an increase in bone resorption and formation in the affected areas. It affects up to 3% of individuals of Anglo-Saxon origin over the age of 40 years but is rare in Arabs. Although most patients are asymptomatic, a variety of symptoms and complications may develop directly from bone involvement or secondarily to compression by bone expansion and increased blood flow. The disease can be treated by using medications that inhibit bone resorption, such as calcitonin and the bisphosphonates. Here we describe the case of an Omani patient with the disease, involving the skull, spine, pelvis, and tibia. He presented to the endocrine clinic in Sultan Qaboos University Hospital with a six-year history of headache, bone pain, progressive skull enlargement, and left-sided deafness. His alkaline phosphatase (ALP) level was 1500 U/L. His disease responded gradually to six months of subcutaneous and nasal calcitonin followed by a single 5 mg intravenous injection of zoledronic acid. This resulted in a further progressive reduction of his bone pain, skull size, and improvement in his hearing, as well as normalization of his serum ALP levels after one-year. This effect has been sustained for 3 years.